IDENTIFIKASI BAKTERI COLIFORM PADA ES BATU DAN ES KRISTAL YANG DIGUNAKAN PENJUAL JUS BUAH DAN WARUNG DI SEKITAR KAMPUS UNIVERSITAS RIAU SEBAGAI POTENSI PENGEMBANGAN BAHAN AJAR MODUL PADA PEMBELAJARAN BIOLOGI SMA - Sumarni '; Irda Sayuti; Evi Suryawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the identification of Coliform bacteria in the ice cubes and ice crystals used fruit sellers and stalls as potential learning module design Biology at a high school in May to June 2016. The research was conducted in two stage laboratory research and design stage of learning modules. This type of research is descriptive and conducted by examination in the laboratory. Sampling technique in this study, done by using purposive sampling method. The results showed that the isolated bacteria found in ice cube consists of five genera, namely Bacillus sp, Pseudomonas, Enterobacter, Citrobacter, and Micrococcus while on ice crystals found in four genera, namely genus Bacillus sp, Enterobacter, Citrobacter and Micrococcus. Based on the analysis of the potential of the research result can be used as the development of the concept Eubacteria module design for high school student.Keywords: Coliform, Ice Cube, Ice Crystal, Module Design